Implementation of Project-Based Learning Method to Enhance English Listening Skills of Computer Science Students at ITB AAS Indonesia - Muliasari, Dewi; Efendi, Tino Feri; Akkapin, Supaphorn (International Journal of Computer and Information System (IJCIS), 2024)
This study aims to evaluate the effectiveness of implementing a project-based learning method in enhancing English listening skills among second-semester Computer Science students at AAS Institute of Business Technology, Indonesia. This method was chosen for its active learning approach that can increase student engagement and language proficiency development. The research employs a quantitative approach with a pre-test post-test control group experimental design. The research sample consists of two groups: an experimental group receiving project-based learning and a control group receiving conventional instruction. Data collection includes English listening tests administered before and after the learning intervention. The findings are expected to provide insights into the effectiveness of project-based learning methods in the context of English language education within the technology education setting in Indonesia.